Challenges and Prospects of Coupling Physical and Human Geography - Ye Chao (Redai dili, 2024)
Major natural and social problems have emerged since the onset of the Anthropocene because of which geography, as a typical interdisciplinary field, has faced unprecedented challenges and opportunities. Given its focus on the complex human-nature relationship, it is necessary to overcome the dualism bias between physical and human geography and prioritize the study of coupling human-nature relationship within the discipline. In the context of Chinese geography, the key and the biggest difficulty of such coupling lies in the methodology used. To solve these major problems, the geographical community should encourage participation in diversified interdisciplinary research and promote the integration of data, technology, and society to bring about a new paradigm of governance science. This shift entails a gradual departure from the prevailing disciplinary evaluation orientation that tends to prioritize physical sciences over social sciences and humanities. Coupling physical and human geography and collaboration between geography and other disciplines are necessary to overcome the common global sustainable development issues.